2016
DOI: 10.1016/j.fishres.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Investigating bias in recreational fishing surveys: Fishers listed in public telephone directories fish similarly to their unlisted counterparts

Abstract: Investigating bias in recreational fishing surveys: Fishers listed in public telephone directories fish similarly to their unlisted counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the choice of the measure of central tendency may not be the only source of bias in the estimation of MRF expenses, as revealed by the mean values estimated in other regions of Spain (Gordoa et al, 2004;Soliva, 2006;García-de-la-Fuente et al, 2020), which double the mean values estimated in this and previously mentioned studies. This might be related to the bias towards more active fishers generated by voluntary participation, which is known as avidity bias (e.g., Thomson, 1991;Teixeira et al, 2016). In general, annual trip-related expenditures per fisher can be expected to be proportional to the frequency of participation (Thomson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice of the measure of central tendency may not be the only source of bias in the estimation of MRF expenses, as revealed by the mean values estimated in other regions of Spain (Gordoa et al, 2004;Soliva, 2006;García-de-la-Fuente et al, 2020), which double the mean values estimated in this and previously mentioned studies. This might be related to the bias towards more active fishers generated by voluntary participation, which is known as avidity bias (e.g., Thomson, 1991;Teixeira et al, 2016). In general, annual trip-related expenditures per fisher can be expected to be proportional to the frequency of participation (Thomson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…1c). Teixeira et al (2016) showed that there was no significant difference in the fishing activity of fishers listed in the phonebook and unlisted fishers.…”
Section: Sensitivity To the Magnitude Of Biasesmentioning
confidence: 97%
“…We analysed charter fishery data in a similar manner to the commercial data, because it is reported as weight per species per year per region in logbooks. The recreational data we accessed through Qfish was collected through a phone call survey 40 . Data from surveys conducted in 2010 24 and 2013 41 were combined to represent the catch of coral-associated species by recreational fishing regions.…”
Section: Data and Analysis For Charter And Recreational Fisheriesmentioning
confidence: 99%